Prejudicial Motherhood in Armando Lucas Correa’s Novel The Daughters’s Tale (2019) - Sherina Alsyifa Amran; Desvalini Anwar (English Language and Literature, 2023)
This thesis analyzes a novel entitled The Daughters' Tale (2019) by Armando Lucas Correa. This analysis reveals prejudicial motherhood experienced by a mother trying to keep her daughters safe from persecution found in the literary work. This analysis uses the psychoanalysis theory by Sigmund Freud to explain the problems of this novel. The result of the study shows Amanda Sternberg experienced prejudicial motherhood in two ways, difficulties to make right decisions and perilous decisions, and it has several effects such as family separation and the death of Amanda Sternberg.